1843 Ind. Acts 982 - (:unkn) unknown (My University, 1843)
Ch. 53, sec. 107: Prohibited the concealed wear or carry of any dirk, pistol, sword in a cane, or other dangerous weapon. Violators fined not exceeding one hundred dollars.
Keywords: CARRY - CONCEALED